KONSEP TAHFIZHUL QURAN PERSPEKTIF ABDUL MU’THI MUHAMMAD RIYADH THULAIMAT DAN IMPLEMENTASINYA DI MA'HAD 'ALY TAHFIZHUL QURAN NASHIRUL QURAN - Din Muhammad Zakariya; Muhammad Farid Fahrudin (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2023)
During the last fifteen years the field of Al-Quran has been in demand by many educational institutions. One of the many educational institutions in the field of Al-Quran that was born is Ma'had 'Aly Tahfizhul Quran Nashirul Quran. In a duration of only two years this educational institution was able to graduate more than fifteen of its students. The factor that has the most influence on this is the implementation of the concept of tahfizh Al-Quran which was compiled by adopting the concept of tahfizh Al-Quran Abdul Mu'thi Muhammad Riyadh Thulaimat. The concept of tahfizh Al-Quran for a limited duration that can accommodate memorization and understanding is a very interesting point. It is interesting to study, analyze and formulate so that it can become an example to be implemented in various other Al-Quran educational institutions in Indonesia. The research objective here is to describe Abdul Mu'thi's tahfizh concept and its implementation in Nashirul Quran. Therefore this research is a descriptive research, namely research that describes a particular phenomenon, event or event with qualitative data. Data analysis in this study uses an interactive data analysis model. Namely through interviews, observation, and documentation. This study concludes that Abdul Mu'thi's concept of tahfizh Al-Quran comprehensively includes five methods of memorizing the Koran, namely talqin, tasmi', muraja'ah, tajwid and tafsir without neglecting the guardianship of students and evaluation of various problems in halakah format Al-Qur'an. The implementation of this concept in Nashirul Quran is well adopted with various modifications. This implementation is supported by sufficient quantity of halakah management resources and adequate infrastructure but not yet 100% optimal because it is hampered by the existence of limits on the length of education and the quality of halakah management resources that do not meet the criteria.